2016
DOI: 10.1097/pec.0000000000000708
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Intravenous Rehydration Therapy in Children With Acute Gastroenteritis

Abstract: Standard volume IV rehydration for 1 to 4 hours followed by oral hydration or maintenance IV fluids seems sufficient for most children with gastroenteritis requiring IV fluid administration. However, more evidence is needed to establish an optimal IV rehydration regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 12 publications
0
12
0
4
Order By: Relevance
“…Potential weaknesses include the possibility of undetected unpublished work, non-inclusion of non-English studies and the heterogeneity in identified studies precluding a formal meta-analysis to augment the systematic review. Another review has recently been published with similar conclusions for management of AGE in emergency rooms in high income (HMIC) settings [ 22 ]. However, our review sought to address the global burden of disease and treatment challenges for AGE rehydration and, given the paucity of data, we can only conclude that robust trials are long overdue.…”
Section: Discussionmentioning
confidence: 97%
“…Potential weaknesses include the possibility of undetected unpublished work, non-inclusion of non-English studies and the heterogeneity in identified studies precluding a formal meta-analysis to augment the systematic review. Another review has recently been published with similar conclusions for management of AGE in emergency rooms in high income (HMIC) settings [ 22 ]. However, our review sought to address the global burden of disease and treatment challenges for AGE rehydration and, given the paucity of data, we can only conclude that robust trials are long overdue.…”
Section: Discussionmentioning
confidence: 97%
“…Refer to the correction of dehydration using a large volume of fluids over a relatively shorter time (50-60 ml/kg/hour). Ultra-rapid IV rehydration may be associated with electrolyte abnormalities and longer hospital stay or delayed discharge and therefore is not recommended [29,30].…”
Section: Rapid Large-volume IV Rehydrationmentioning
confidence: 99%
“…Eine weitere prospektiv randomisierte Studie zeigte weder für die Verwendung von Ringer-Laktat noch einer 0,9 %igen NaCl-Lösung bei schwer dehydrierten Kindern eine Entwicklung von Hyper-oder Hyponatriämien [128]. [129,130]. Die Autoren empfehlen eine Rehydration mit 20 ml/kg/h über 1 bis 4 Stunden gefolgt von oraler Hydrierung bzw.…”
Section: Ii28 Empfehlungunclassified